Solitary pancreas transplantation: a review of the UK experience over a period of 10 yr. (18th November 2015) - Vrakas, Georgios; Arantes, Rubens Macedo; Gerlach, Undine; Reddy, Srikanth; Friend, Peter; Vaidya, Anil
Abstract: Background: The aim of this study was to see whether lessons could be learned from the prospectively maintained nationwide database on solitary pancreas transplantation (SPTx) performed in the UK. Methods: Two hundred and forty‐five SPTx were utilized from the 2004–2013 period (113 pancreas transplant alone and 132 pancreas after kidney). The statistical analysis included donor, recipient, transplant variables, and the effect of a rejection episode on graft survival. Results: Cold ischemia time (CIT), CIT > 12 h, donor body mass index (BMI) > 30, and non‐lymphocyte‐depleting induction immunosuppression achieved p‐value <0.05 in the unadjusted univariate hazard model analysis. In a multivariate analysis, variables that persisted in demonstrating increased independent risk included CIT > 12 h (hazard ratio [HR] 1.94, p = 0.035) and the use of non‐depleting induction immunosuppression (HR 1.95, p = 0.002). Factors such as bladder‐drained grafts and donor variables including age, BMI, and donation after cardiac death (DCD) vs. donation after brain‐stem death did not attain significance. Rejection reduces the overall graft survival by approximately 1000 d (1841 ± 114 d vs. 915 ± 119 d, p = 0.001). Conclusions: Cold ischemia time <12 h and the use of depleting antibodies as induction immunosuppression have a positive effect on pancreas allograft survival. Other factors such as bladder‐drained grafts and donor variables such as age, BMI, and DCD status did not attain significance in a multivariate analysis.